* Cộng :
(+) + (-) = (-)
(-) + (+) = (-)
(-) + (-) = (+)
(+) + (+) = (+)
* Trừ
(-) - (-) = (-)
(+) - (+) = (-)
(-) - (+) = (+)
(+) - (-) = (+)
* Cộng :
(+) + (-) = (-)
(-) + (+) = (-)
(-) + (-) = (+)
(+) + (+) = (+)
* Trừ
(-) - (-) = (-)
(+) - (+) = (-)
(-) - (+) = (+)
(+) - (-) = (+)
\(\left(+\right)+\left(-\right)=\left(-\right)\)
\(\left(-\right)+\left(+\right)=\left(-\right)\)
\(\left(-\right)+\left(-\right)=\left(+\right)\)
\(\left(+\right)+\left(+\right)=\left(+\right)\)
\(\left(-\right)-\left(-\right)=\left(+\right)\)
\(\left(+\right)-\left(+\right)=\left(-\right)\)
\(\left(-\right)-\left(+\right)=\left(+\right)\)
\(\left(+\right)-\left(-\right)=\left(+\right)\)